Political uncertainty and economic underdevelopment - Streb, Jorge (Estudios de Economía, 2016)
Political instability has been emphasized as a major source of uncertainty in Latin America. However,arbitrariness, i.e. the lack of constraints on the government, can also be seen as a major source of uncertainty in developing countries. Two dimensions of political uncertainty are thus distinguished, instability and arbitrariness. Empirically, low polity persistence is used for political instability, and low political constraints are used for arbitrariness. Unlike the usual approach in the literature, I relate this specific measure of political uncertainty to income per capita, rather than growth. The reason to explore this link is that if uncertainty leads to high interest rates, both capital and income per capita should be low. The conjecture that steady state income is lower with high political uncertainty leads to focus on its two dimensions. The data indeed suggest a strong positive relationship of political certainty, i.e. the combination of political constraints and polity persistence, with income per capita. Economic convergence may be conditional on the gradual process of elimination of political uncertainty.